Chewable tablet with herbal extracts and propolis arrests Wuhan and Omicron variants of SARS-CoV-2 virus - Karaoglu, Oznur; Serhatli, Muge; Pelvan, Ebru; Karadeniz, Bulent; Demirtas, Ilknur; Cakirca, Gamze; Sipahi, Hande (Elsevier, 2023)
Prevention of COVID-19 is of paramount importance for public health. Some natural extracts might have the potential to suppress COVID-19 infection. Therefore, this study aimed to design a standardised, efficient, and safe chewable tablet formulation (with propolis and three herbal extracts) for possible prevention against two variants (Wuhan B.1.36 and Omicron BA.1.1) of SARS-CoV-2 virus and other viral infections. Green tea, bilberry, dried pomegranate peel, and propolis extracts were selected for this purpose. Cytotoxicity and antiviral activity of each component, as well as the developed chewable tablet, were examined against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus using Vero E6 cells with the xCELLigence real-time cell analysermultiple plates system. Anti-inflammatory and analgesic activities, as well as mutagenicity and antimutagenicity of the chewable tablet were also analysed. Compared to the control, it was observed that the chewable tablet at concentrations of 110 and 55 mu g/mL had antiviral activity rates of 101% and 81%, respectively, for the Wuhan variant and 112% and 35%, respectively, for the Omicron variant. The combination of herbal extracts with propolis extract were synergically more effective (similar to 7-fold higher) than that of individual extract. The present work suggests that a combination of herbal extracts with propolis at suitable concentrations can effectively be used as a food supplement for the prevention of both variants of the SARS-CoV-2 virus in the oral cavity (the first entry point of the SARS-CoV-2 virus).
Keywords: COVID-19; Chewable tablet; Antiviral; Cytotoxicity; Extracts; Propolis; Phenolics